The Role And Partisanship Of The Inner Bandung City Government Responding To Land Disputes On Jalan Anyer Dalam, Kel. Kebonwaru, District. Batununggal, Bandung City - Fadli Alfikri; Idil Akbar (POLITICO, 2023)
Agrarian conflict is a problematic issue that still exists and occurs today. One of them is the land dispute case that occurred in Anyer in Bandung City. The conflict involved the Anyer Dalam community and PT. KAI are claiming land in the Anyer Dalam area. In agrarian conflicts, the role and alignment of the government is very important. Therefore, the author conducted research using a literature study method and a qualitative descriptive research method to see the role and alignment of the Bandung City Government in the land dispute in Anyer Dalam. From the research results, it can be concluded that the Bandung City Government has not been able to carry out its role well and the Bandung City Government's partiality deserves attention, because the government tends to make things difficult for the community in this conflict.